In vitro antibacterial activity of patchouli batik (Pogostemon Cablin) plant extract varieties from Southeast Sulawesi and South Sulawesi - Tuty Yuniarty; Ratih Feraritra Danu Atmaja; Julianti Isma Sari Usman; Theosobia Grace Orno (Jurnal Teknologi Laboratorium)
Indonesia has biodiversity traditional medicinal plants. One of the plants used is patchouli Batik (Pogostemon cablin) from South Konawe, Southeast Sulawesi and patchouli from Bulukumba, South Sulawesi. This experimental research aimed to determine the effect of stem and leaves extracts of patchouli Batik from South Konawe, Southeast Sulawesi and patchouli from Bulukumba, South Sulawesi, on Escherichia coli, Staphylococcus aureus and Streptococcus mutans using the diffusion method (Kirby-bauer). The diffusion test was expressed as the width of inhibition zone in millimetres The results showed that the total flavonoid content of the leaves and stems of patchouli Batik from South Konawe, Southeast Sulawesi was 301.823 mg QE/gr and 119.905 mg QE/gr, and the total flavonoid content of the leaves and stems of patchouli from Bulukumba, South Sulawesi was 474.120 mg QE/gr and 148.856 mg QE/gr. The phenolic content of the leaves and stems of patchouli batik from South Konawe, Southeast Sulawesi was 420.22 mg GAE/gr and 411.55 mg GAE/gr, while the phenolic content of the leaves and stems of patchouli from Bulukumba, South Sulawesi was 818.13 mg GAE/gr and 227.77 mg GAE/gr. Stem and leaves extracts have antibacterial effects on Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 43300, Streptococcus mutans ATCC 35668 with the largest diameter found in samples of Patchouli batik leaves extract with concentration of 100% in Streptococcus mutans bacteria of 16 mm, Escherichia coli bacteria of 15 mm and in patchouli leaves extract. from Bulukumba with concentration of 100% in Staphylococcus aureus bacteria was 15 mm.